Manajemen Laba dan Perilaku Investasi: Apakah Framing Effect Diperhitungkan? - Kurniawan, Firdaus; Amanati, Hilma Tsani; Pusparini, Nandya Octanti; Mukti, Meliani (E-Jurnal Akuntansi, 2021)
This study aims to obtain empirical evidence on the effect of earnings management on company's investment decision making, as well as to see indications of the framing effect caused by earnings management on the company's investment behavior. The sample of this study includes all manufacturing companies listed on the stock exchanges of countries in Southeast Asian region with an observation period from 2009 to 2019. The results indicate a positive and significant effect of earnings management on management investment decisions. Meanwhile, the framing effect is believed to arise as a result of earnings management practices and also influences managers in viewing further as a consideration for making company investment decisions. Keywords: Earnings Management; Investment Decision; Framing Effect.